Subtitling History Cultural and Temporal Transfer in a Heritage Film Oliver Twist (2005) - Liang, Lisi (Journal of Audiovisual Translation, 2020)
The paper will focus on how history is reshaped in a case study: the film adaptation of Oliver Twist (2005). It is of significance as its Chinese authorised subtitles mediate nineteenth-century British history for a contemporary Chinese audience. But this adaptation creates various problems of translation as it negotiates the cultural and linguistic transfer between early Victorian England and twenty-first-century China. To illustrate the challenge that translators and audiences face, examples drawn from the subtitles are grouped under Eva Wai-Yee Hung’s (1980) suggested aspects of Dickens’s world: “religious beliefs, social conventions, biblical and literary allusions and the dress and hairstyle of the Victorian era”. Moreover, Andrew Higson’s “heritage” theory (1996a), William Morris’s (Bassnett, 2013) views of historical translation and Nathalie Ramière’s (2010) cultural references specific to Audiovisual Translation are adopted to read the Chinese subtitles. They are used to bring back the audiences to an impossible, inaccessible past. The historical features shown in this modern version of a British heritage film make it possible for the subtitles to interact with Chinese culture to transfer meaning via a complex combination of translation strategies. Therefore, in order to rejuvenate Chinese cultural heritage, the subtitles of the cultural and temporal specificities and complexities involved are reinterpreted and redirected to the receiving culture